Multi-instrument observations of the ionospheric response to the 26 December 2019 solar eclipse over Indian and Southeast Asian longitudes - Barad, R.K.; Sripathi, S.; England, S.L. (My University, 2022)
Here, the impact of the 26 December 2019 solar eclipse on the equatorial and low latitude ionosphere has been investigated using ground and space-based observations over Indian and Southeast Asian longitudes. The high-resolution Ionosonde observations at Tirunelveli, GPS Total Electron Content (TEC) observations from a chain of GPS receivers along and across the eclipse path, TIMED-SABER, and Ionospheric Connection Explorer (ICON) satellites were utilized to investigate the eclipse-induced variations in electron density and thermospheric cooling. We noticed a tremendous increase and decrease in the base height of the F-layer, resembling the nighttime Pre-Reversal Enhancement (PRE). Near the eclipse maximum, a strong blanketing sporadic E layer was observed at Tirunelveli with a top frequency of ∼18 MHz for 1 hr and 26 min. Satellite traces (STs) and “U” shaped ionograms were noticed for the first time over Tirunelveli during eclipse maximum and end phases. The “STs” and “U” shaped traces indicate the presence of short-period gravity waves or TID type of wave perturbations over the Indian region. A maximum of ∼5–7 TECU (30%–40%) decrease in TEC is observed on the eclipse day for iisc, hyde, and tiru stations. Periodogram analyses of TEC data showed the presence of wavelike structures with periodicities of 18–24 min for different stations. Simultaneous observations from the ICON satellite showed an increase and decrease in hmF2 and NmF2 which matches well with the ionosonde observations from Tirunelveli. The temperature profiles from TIMED-SABER and ICON satellites showed a reduction and enhancement in the lower and upper E regions respectively.
Keywords: Solar eclipse; Indian longitudes; 26 December 2019 Solar Eclipse; Southeast Asian longitudes